Hungarian Monitoring, 25 April 1988 . [Magyar rádiófigyelő], 1988. április 25 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - First round of the French presidential elections - Schultz in talks in Brussels - Syrian-PLO relations - Strikes in Poland Domestic Affairs: - Grósz gives interview to Der Spiegel - Kádár welcomes John McLaughlin, American TV personality - Backhanders - Szálasi trial materials released - Secretary of the Lutheran World Federation visits Hungary - IKV director's corruption in post Economy: - Hungarian National Bank profits fall by over one half Külpolitika: - A francia elnökválasztás első fordulója - Schultz Brüsszelben tárgyal - Szíria és a PFSZ viszonya - Sztrájkok Lengyelországban Belpolitika: - Grósz interjút adott a Der Spiegelnek - Kádár fogadta John McLaughlin amerikai tv - Személyiséget - Hálapénz - Kiadják a Szálasi-per anyagát - Lutheránus Világszövetség főtitkárának látogatása - Az IKV igazgató hivatali megvesztegetése Gazdaság: - A MNB nyeresége több, mint a felével csökkent